Comprehensive Surgical Staging in Stage 1 Clear Cell and Endometrioid Ovarian Carcinomas: Is it Necessary?. (May 2019) - Padhy, Radha R.; Savage, Johanna; Kurman, Robert J.
Abstract : The objective of this article was to evaluate the presence of occult metastasis after comprehensive surgical staging of clear cell ovarian carcinoma (CCC) and endometrioid ovarian carcinoma (EMCA) that appeared to be confined to the ovary at time of surgery. Between 1998 to 2016, 85 patients with CCC and EMCA were identified who were comprehensively staged and felt to be stage 1 intraoperatively. Of the 85 patients who underwent surgical staging, 4 (4.7%) had omental and dense pelvic side-wall tumor adhesions. On final pathology, 67 (79%) patients were diagnosed as stage 1A of which 29 (43%) patients were upstaged to 1C1 due to intraoperative rupture. The remaining 18 (21%) patients were staged as 1C2/1C3. The 1- and 5-yr disease-free survival for pathology stage 1A tumors was 94% and 76%, respectively, and for 1C2/1C3 tumors was 100% and 75%, respectively. Among patients who received adjuvant chemotherapy, the 5-yr disease-free survival was near equal for pathology stage 1A and 1C2/1C3 groups (73% vs. 74%), with a lower 5-yr disease-free survival for CCC compared with EMCA (72% vs. 78%). There were 16 (19%) recurrences with 12 being pathology stage 1A. Of these 12 patients, 9 (75%) had CCC of which 2 received adjuvant chemotherapy. Even in the presence of dense adhesions (4.7%), the likelihood of extraovarian disease in CCC and EMCA confined to the ovary was very low. Accordingly, the findings in this study indicate that comprehensive surgical staging for what appears to be stage 1 CCC and EMCA may provide no benefit in detecting occult disease that would upstage the tumor.